Promising opportunities to improve polio vaccines - E. E. Evreinova; L. M. Khantimirova; V. A. Shevtsov; V. A. Merkulov; V. P. Bondarev (Биопрепараты: Профилактика, диагностика, лечение)
Polioviruses belong to Enterovirus C species and cause severe lesions of the nervous system. In the post-polio eradication era, the World Health Organisation recommends inactivated polio vaccines for effective long-term protection of the population. In order to meet the needs of global health, it is planned to increase the use of traditional and optimised inactivated polio vaccines and introduce new types of vaccines that are being developed based on the current understanding of RNA-containing viruses. The aim of the study was to analyse ways of improving vaccine preparations and to review promising areas for polio immunoprophylaxis development. The authors considered innovations across all stages of the technological process, aimed at obtaining optimised vaccines, as well as vaccine delivery systems. The article presents information on new vaccine strains and cell lines for vaccine production. The authors summarised the results of clinical studies of inactivated vaccines, new vaccines based on genetically stable vaccine strains of poliovirus, and vaccines containing virus-like particles. The most likely candidates for introduction are the vaccines based on virus-like particles obtained from genetically modified strains of poliovirus. At the moment, many issues related to current trends in improving the immunoprophylaxis of poliomyelitis are debatable and need to be addressed in the near future.